Fibrinogen and cardiovascular disease: genetics and biomarkers. - Tousoulis, D; Papageorgiou, N; Androulakis, E; Briasoulis, A; Antoniades, C; Stefanadis, C (2011)
Several prospective epidemiological studies and clinical observations provided evidence regarding fibrinogen and coronary artery disease (CAD). Many of these studies firmly correlate fibrinogen with CAD. However, it is uncertain whether this relation is causal or reflects genetic variability and residual confounding by other risk factors. Several polymorphisms on fibrinogen chain genes affect its levels, however only few of the genetic variants are associated with increased cardiovascular risk. As regards the role of fibrinogen in myocardial infarction (MI) studies indicate that genetic variations have at best a modest impact on the process resulting in MI. Therefore, the screening of fibrinogen genes might not be useful for the assessment of the risk of MI. However, the findings that specific genotypes lead to specific differences in fibrinogen levels, but may not be linked to cardiovascular risk, complicates the hypothesis of causality of fibrinogen in the pathogenesis of cardiovascular disease.